A Web Simulator to Assist in the Teaching of Bayes' Theorem. Issue 2 (4th May 2019) - Bárcena, M. J.; Garín, M. A.; Martín, A.; Tusell, F.; Unzueta, A.
Abstract: Teaching some concepts in statistics greatly benefits from individual practice with immediate feedback. In order to provide such practice to a large number of students we have written a simulator based on an historical event: the loss in May 22, 1968, and subsequent search for the nuclear submarine USS Scorpion . Students work on a simplified version of the search and can see probabilities change in response to new evidence. The simulator is designed to assist in the teaching of Bayesian concepts, in particular Bayesian updating. It has been deployed in our courses and our experience and results are described, as well as the reactions of our students to its use. The simulator is open source, freely available and easy to implement and run, as it only requires a machine to serve web pages. We explain in detail our experience with its deployment and use.